Analysis of Money Laundering by Applying a Pyramid Scheme System in Distributing Goods” With Fraud Mode (Case Study Of Supreme Court Decision No. Number 4202 K / Pid.Sus/2023) - Maswandi, Maswandi (International Asia Of Law and Money Laundering (IAML), 2025)
This study is intended to analyze the modus operandi used and how consideration of judges in the settlement of cases of money laundering, as well as countermeasures can be done against business fraud crimes that apply pyramid schemes in Supreme Court decision number 4202 K / Pid.Sus/2023 . Juridical method empirical is used in tracing data sourced in normative research. The results of the study produced the cause mode of money laundering with the origin of fraud businesses that implement pyramid schemes is public ignorance of good investment or wrong. Consideration of judges in the settlement of cases of business fraud that apply the scheme pyramid, stating that this crime is proven to violate the actions of the defendant as set and threatened in Article 378 of the criminal code in conjunction with Article 55 Paragraph (1) to-1 of the Criminal Code;. Attempts countermeasures can be done with pre-emtive efforts, namely the implementation of routine socialization and provision program for good investment, further preventive efforts through increased supervision and implementation of inspections of businesses that have permission or not to invest heavily in society, as well as repressive efforts in the form of sanctions, enforcement and punishment of punishment.